National standards: Reasserting the ecological restoration framework in uncertain times - McDonald, Tein; Dixon, Kingsley (Wiley-Blackwell Publishing Ltd, 2018)
© 2018 Ecological Society of Australia and John Wiley & Sons Australia, Ltd National ecological restoration standards – produced in 2016 through the collaboration of 13 of Australia's leading ecological restoration organisations – are increasingly influencing practitioners. This paper elucidates two of the Key Principles that underpin standards to encourage highest and best efforts across all sectors and help resolve uncertainty about the role of restoration in a changing world.